Exploring indicators of subjective well-being for first-year university students. Issue 5 (3rd September 2019) - Botha, Bianca; Mostert, Karina; Jacobs, Melissa
Abstract : This study aimed to explore indicators of subjective well-being among first-year university students attending a South African university ( N = 11; female = 6, black = 6, age range = 19 to 22). Participants shared their experiences of university life by participating in group sessions using the Mmogo method ® and semi-structured interviews. Following thematic analysis, findings showed subjective well-being in the student population to be indicated by: (i) emotional well-being states of positive and negative affect and satisfaction with life and the university; (ii) psychological well-being of meaning and purpose in their studies, mastery, personal growth, self-acceptance, and independence; (iii) social well-being qualities of opportunities for social engagement, positive relations with others, and inclusivity through exposure to diversity, acceptance of others, and a sense of belonging; (iv) spiritual indicators, especially opportunities to engage in spiritual practices; and (v) physical well-being, indicated by sleeping patterns, dietary habits, and physical activity. Factors influencing students' experience of well-being included structural resources provided by the university, information and communication, motivation to graduate, choice of academic course, lecturers and facilitators, and uncertainties. Student's self-perceptions of well-being are important for improving their quality of life of attending university.